Analysis of the Influence of Financial Literacy and Management Accounting on Financial Performance through Digital Marketing in MSMEs - Ni Nyoman Yuliati; I Made Suardana; Sofiati Wardah; Indah Ariffianti; Baiq Ertin Helmida (Greenation International Journal of Economics and Accounting, 2026)
This study aims to analyze the influence of financial literacy and management accounting on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) with digital marketing as a mediating variable in the context of MSMEs in West Nusa Tenggara Province (NTB). This study uses a quantitative, explanatory design and is analyzed using Structural Equation Modelling based on Partial Least Squares (SEM-PLS) with SmartPLS. Data was collected through a survey of 280 MSME actors. The results of the study show that financial literacy and management accounting have a positive and significant effect on the financial performance of MSMEs. Digital marketing has been shown to have the strongest influence on financial performance. It plays a significant role in the relationship between financial literacy and management accounting. In addition, financial literacy and management accounting also have a significant effect on digital marketing. These findings confirm that improving the financial performance of MSMEs depends not only on internal resources but also on the ability to leverage digital capabilities. This research provides a theoretical contribution by integrating the Resource-Based View and Dynamic Capabilities to explain MSME performance. It offers practical implications for business actors and policymakers to increase MSME competitiveness in the digital era, especially in developing areas such as NTB.